Integrating Arabic Fun Video Media with Round Table Learning Model on Students’ Outcomes in Arabic Lessons - Dienana, Arina; Asep Sopian; Uswah Mujahidah Rasuna Sa’id; Aji Rizqi Ramadhan; Widad Nur Fauziyyah (Arabiyatuna : jurnal bahasa Arab (Online), 2025)
This study aimed to examine the effect of integrating Arabic Fun Video learning media with the Round Table teaching model on students’ vocabulary comprehension in Arabic language lessons at Madrasah Diniyyah Mafaza Lubuk Linggau. Arabic is one of the compulsory subjects at the institution; however, the learning process still encounters several challenges. Students exhibit limited understanding of Arabic language materials, and the lack of instructional media has contributed to a decline in their engagement during lessons. To address these issues, it is essential for teachers to employ innovative and interactive media, along with effective learning models, to foster a conducive and focused classroom environment. Research in educational psychology underscores that creative and interactive learning tools can enhance student motivation, engagement, and academic achievement. This study employed a quantitative approach with a quasi-experimental design, specifically a non-equivalent group design. The sample consisted of 30 students, selected through purposive sampling. The research instrument was a vocabulary test that had undergone validity and reliability testing. Validity was assessed using Pearson’s Product Moment correlation, while reliability was measured with Cronbach’s Alpha coefficient. Data were analyzed using an independent samples t-test, as the data met the assumptions of normality and homogeneity. The findings revealed that the integration of Arabic Fun Video media with the Round Table model significantly enhanced students’ learning outcomes in Arabic. Statistical analysis indicated a significant difference between the experimental and control groups (t-test, Sig. 0.020 < 0.05).